2015
DOI: 10.1007/s13365-015-0324-4
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Montreal Cognitive Assessment and the HIV Dementia Scale in the assessment of cognitive impairment in HIV-1 infected patients

Abstract: The gold standard for evaluating cognitive impairments in HIV-infected patients is to administer an extensive neuropsychological assessment. This may, however, be time-consuming and hence not always feasible in the clinic. Therefore, several brief screening tools have been developed. This study determined the validity of the Montreal Cognitive Assessment (MoCA) and the HIV Dementia Scale (HDS) in detecting cognitive impairment using both the Frascati and cognitive impairment, no dementia (CIND) criteria to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
1
31
3
8
Order By: Relevance
“…We found a cut-off of ≤26 as the most optimal balance of sensitivity and specificity, which is somewhat higher than the ≤25 cut-point found in other studies in HIV (Chartier et al, 2015; Hasbun et al, 2012; Janssen et al, 2015; Ku et al, 2014; Milanini et al, 2014; Overton et al, 2013). Moreover, the optimal MoCA cut-off remained the same when participants with significant confounding neuromedical factors (e.g., history of stroke, severe head injury) were excluded from analyses.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…We found a cut-off of ≤26 as the most optimal balance of sensitivity and specificity, which is somewhat higher than the ≤25 cut-point found in other studies in HIV (Chartier et al, 2015; Hasbun et al, 2012; Janssen et al, 2015; Ku et al, 2014; Milanini et al, 2014; Overton et al, 2013). Moreover, the optimal MoCA cut-off remained the same when participants with significant confounding neuromedical factors (e.g., history of stroke, severe head injury) were excluded from analyses.…”
Section: Discussioncontrasting
confidence: 73%
“…Therefore, patients identified as having possible impairment by the MOCA should be referred for a comprehensive evaluation to more accurately characterize and diagnose neurocognitive abilities. By some criteria (as used in the Janssen et al, 2015 study), sensitivities less than 80% and specificities less than 60% are not considered adequate (Blake, McKinney, Treece, Lee, & Lincoln, 2002; Janssen et al, 2015). Thus, using those criteria, while our sensitivity (i.e., 84%) would be considered adequate, our specificity (i.e., 56%) was below the threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in the US found results close to those of Joska, 109 while work in the Netherlands showed similar high sensitivity and low specificity only when used at a cut-off of 28.5; at standard cut-off, both statistics were closer to 60%. 110 In the Dutch study, the area under the receiver-operator curve suggested that the MoCA was diagnostically similar to the HDS. In contrast, several other studies, including one recruiting only participants aged >60 years and one using a locally modified version in Korea, have also reported lower sensitivity but higher specificity.…”
mentioning
confidence: 95%